The unintended consequences of tax treaties and the unfair allocation of treaty taxing rights from a developing country’s perspective - Oguttu, Annet Wanyana (University of Pretoria, 2021)
Mini Dissertation (MPhil (International Taxation))--University of Pretoria, 2020.